MEDIA SENI SEBAGAI SARANA MELEPASKAN STRES PARA IBU PKK CILINCING - Runi Michiko; Jacqualyne Gavrilla Kumayas; Syiefa Atharida Pertiwi; Denrich Suryadi (Jurnal Serina Abdimas, 2025)
Cilincing subdistrict, located in Cilincing District, North Jakarta City. Cilincing subdistrict has a family welfare promoter that does activities for children and women. Family welfare promoters consist of housewives who spare their time between family and duties for humanity. As a mother that is also active in family welfare promotion, they experience mental pressure such as stress. Stress is an impact for taking care of family and welfare promoter activities.. The purpose of this activity is to improve the mental health of family welfare promoters. The number of our respondents was 13 people. The measuring instrument used was the Perceived Stress Scale Version 10 (PSS-10). Based on PSS-10 data processing, the result was 19, which means they experience moderate stress. In dealing with stress, material about stress and doing art activities was given to express the emotion. This humanity project was carried out for 18 days, from Tuesday, February 18, 2025, to Tuesday, April 15, 2025. On 18 February we followed and observed their activities. The intervention was carried out within 2 meetings. The intervention was carried out in 2 meetings on Tuesday, April 8, 2025, by providing a pretest, material on stress, and painting. Then the second meeting on Tuesday, April 15, 2025, by providing material on emotional management, painting, and a posttest. The results showed that there was no significant decrease in stress level, with the mean score decreasing only slightly from 19 to 18.5, which still falls within the moderate range. Therefore, it can be concluded that the activity implemented was not effective. Factors contributing to this ineffectiveness included a lack of cooperation, insufficient rapport, limited understanding of the activity’s objectives, and time to conduct the activity, which led to PKK members being unwilling to open up to the project facilitators.